A Comparison of Economic Performance Between ISO 9001 Certified and Non-ISO 9001 Certified Food Manufacturing Companies - Aravena Andrade, Amanda Victoria (2023)
Only a small group of companies in Peru are certified to the ISO 9001 International Quality Standard, and it is uncertain whether this standard contributes to their financial performance. As a result, the objective of this study was to compare the financial performance of food manufacturing companies certified to ISO 9001 with those that are not. The non-parametric Mann-Whitney U test for median comparison was applied, since the data analyzed did not follow a normal distribution. It was found that there is no statistically significant difference between the financial results of the two groups; however, referring specifically to the asset turnover indicator, companies that have adopted the guidelines of the International Quality Standard, on average, convert their assets into cash more frequently.